Curricular Fundamentals of a Critical Curriculum for the Pre-University Level in Costa Rica - Toruño Arguedas, César (2016)
This essay drafts a proposal for the curricular fundamentals for a critical curriculum in Costa Rica at pre-college level. Still, the premises posed are extrapolated from curricular alternatives might differ from the traditional system. Based on a content analysis of papers in different fields, the pedagogical (Critical Pedagogy), psychological (Vigotsky’s contributions), sociological (Education and Sociology), and historical contextual (interpretation of the context where this education proposal is built) fundamentals are stated. The reflection allows for establishing the viability, pertinence y relevance of these fundamentals for the construction of a coherent curricular alternative for Critical Pedagogy, Critical Curriculum, and the demands of Costa Rican pedagogical progressivism.